Business Sustainability Improvement Model Through Community Capacity Building in Community of Creative Economy Grobogan - Dita Prameswari; Winarsih (JMBPreneur: Jurnal Manajemen, Bisnis, dan Kewirausahaan, 2021)
Background: The rise of the business world today has an impact on the level or number of business actors which is increasing which can lead to tight competition in business. Given these problems, the thing that needs to be considered is how to maintain business sustainability so that it remains sustainable in the long term.Purpose: The purpose of this study is to examine more deeply about the role of capacity in the community towards business sustainability, which focuses on community agreeableness or is defined as a willingness to share in the creative economy community in Grobogan Regency.Methods: The object of this research is the creative economy community in Grobogan Regency which has several small and medium industries in it which are also the population in this study. While the sampling method using purposive sampling as many as 50 respondents. Then the data is collected through a questionnaire which will be processed using the PLS 4.0 analysis technique.Conclusion: From the results of the study, it can be concluded that community agreeableness is an antecedent in increasing business sustainability. This theory can be practiced in the Grobogan creative economy community to increase business sustainability and as an effort to maintain and develop business in an era or dynamic business environment.Suggestion: For the future agenda, it should be carried out with a wider scope and develop variables as determinants of business sustainability in the long term